Kinetics of Carbon Monoxide Oxidation on Solid Oxide Solution and Platinum on Alumina - A Comparative Study - Rajadurai, S.; Carberry, J.J. (Journal of catalysis, 1994)
Catalytic oxidation of carbon monoxide on supported and unsupported noble metal catalysts has been the subject of numerous studies aimed at elucidating reaction mechanism and quantifying its kinetic parameters. The authors studied the kinetics of CO oxidation in excess oxygen (99% O[sub 2]) on supported Pt catalyst and solid oxide solution La[sub 0.8]Sr[sub 0.2]CrO[sub 3[minus][sigma]] (ND1) as a function of CO concentration. The comparison between the kinetics of the catalytic behavior of Pt/alumina and solid oxide solution La[sub 0.8]Sr[sub 0.2]CrO[sub 3[minus][sigma]] and the dependency of the turnover velocity coefficient of CO oxidation upon dispersion on Pt/alumina catalysts with different sintering severity are reported. 20 refs., 3 figs., 2 tabs.